Biological and structural characteristics of the binding peptides from the sporozoite proteins essential for cell traversal (SPECT)-1 and -2 (2011)
The sporozoite microneme proteins essential for cell traversal, SPECT-1 and SPECT-2, are considered attractive pre-erythrocytic immune targets due to the key role they play in crossing of the malaria parasite across the dermis and the liver sinusoidal wall, prior to invasion of hepatocytes. In this study, the sequences of SPECT-1 and SPECT-2 were mapped using 20 mer-long synthetic peptides to identify high-activity binding peptides (HABPs) to HeLa cells. 17 HABPs with enzyme sensitive bindings to HeLa cells were identified: 3 predominantly ?-helical in SPECT-1, and 10 ?-helical and 4 ?-turns/random coils in SPECT-2. Immunofluorescence assays (IFA) with antibodies raised in rabbits against chemically synthesized B-cell epitopes suggests the presence of these two proteins in the micronemes and in sporozoite membrane. 1H NMR studies showed that HABPs located in the membrane-attack complex/perforin (MACPF) domain of SPECT-2 share high similarity with the 3D structure of C8?. Altogether, the results highlight the potential of including HABPs from SPECT-1 and SPECT-2 as components of a fully effective multistage, multiepitopic, minimal subunit-based synthetic vaccine against Plasmodium falciparum malaria. © 2010 Elsevier Inc. All rights reserved.